EKSPLORASI MATERI AJAR PEMBELAJARAN BERBASIS ETNOMATEMATIKA MENGGUNAKAN ONDEL ONDEL KHAS BETAWI DI SEKOLAH DASAR - Siti Maghfira Ramadhani; Desi Setiyadi; Fitriana Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to identify the potential of ondel-ondel, a traditional Betawi puppet,as a medium for teaching mathematics in elementary schools and to examinestudents' enthusiasm while participating in math lessons that are integrated with thislocal cultural element. The research method used is a descriptive qualitative approach with research subjects including the school principal, fifth-grade teachers, and fifth-grade students at SDIT Al Inayah. Data collection techniques were carried out through observation, structured interviews, and documentation. The research results show thatthe structure and ornaments of ondel-ondel contain various mathematical elements,such as algebra concepts, two-dimensional and three-dimensional shapes, symmetry,patterns, and measurements. The use of ondel-ondel as a teaching medium hasproven to increase student activity and enthusiasm as well as aid in understandingmathematical concepts contextually. In addition, the use of local culture-based mediasuch as traditional clothing, traditional houses, traditional games, and traditional foodsalso has the potential to serve as alternative media for teaching ethnomathematics.This learning reinforces local cultural values and supports the character developmentof students in line with the principles of the Merdeka Curriculum. Thus, ondel-ondelbased ethnomathematics can be a relevant pedagogical innovation in enhancing thequality of mathematics education in elementary schools.